2023
DOI: 10.3390/psych5030039
|View full text |Cite
|
Sign up to set email alerts
|

Trafficking Women for Sexual Exploitation: A Systematic Review

Abstract: Human trafficking is a complex global problem that demands current and scientifically grounded knowledge capable of coordinating interventions among various sectors of society. To address this issue, a systematic collection of scientific articles was conducted in two databases (Web of Science and Scielo) using keywords in both English and Portuguese. After screening 267 articles based on title, abstract, and full text, an 11-article sample was analyzed for quality. The results revealed that conceptual inconsis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The demanding nature of medical education, coupled with the stressors inherent in clinical training, exacerbates susceptibility to mental health disorders [19]. To further contextualize these findings, it is imperative to explore the specific types of mental health disorders prevalent among medical students [19,27,28]. Research indicates a spectrum of conditions, including but not limited to anxiety, depression, burnout, and substance abuse [8][9][10].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The demanding nature of medical education, coupled with the stressors inherent in clinical training, exacerbates susceptibility to mental health disorders [19]. To further contextualize these findings, it is imperative to explore the specific types of mental health disorders prevalent among medical students [19,27,28]. Research indicates a spectrum of conditions, including but not limited to anxiety, depression, burnout, and substance abuse [8][9][10].…”
Section: Discussionmentioning
confidence: 99%
“…It looked at the articles' robustness by assessing consistency, title clarity, abstract synthesis, state of the art, objectives, and method analysis for further research [26]. The checklist was modified to include 13 topics ((1) title; The authors adopted a Likert scale of 0 (not reported/not specified), 1 (unclear/reported to some extent), and 2 (adequately reported) [27]. A score of 0 denotes that there is no information in the study about the subject at hand, whilst a score of 1 indicates that the researchers discussed the problem in passing without going into great detail.…”
Section: Quality Appraisal Of the Studymentioning
confidence: 99%
See 1 more Smart Citation